Prevalence of Chronic Otitis Media among Undernourished Children - Shajahan, Shehanaaz; Aroor, Rajeshwary (Journal of Health and Allied Sciences NU, 2020)
Objective This study aimed to identify the role of nutrition in the etiology of chronic suppurative otitis media (CSOM) by comparing the prevalence of CSOM between undernourished children with normal children aged between 10 and 12 years.Materials and Methods A total of 200 children aged between 10 and 12 years studying in government schools were selected for the study. All the children underwent a general and detailed ENT examination in addition to nutritional assessment based on body mass index calculation, using World Health Organization (WHO) Child Growth Standards Chart. The children were divided into two groups: Group A and Group B. Group A consisted of 100 children who were malnourished and Group B consisted of 100 children who were normal. The presence of CSOM in the two groups was noted.Results and Observations Of the total 200 children, 112 were boys (56%) and 88 were girls (44%). Of the 112 boys, 22 (19.64%) had CSOM and out of 88 girls, 24 (27.27%) had CSOM. Of the total 46 children found to have CSOM, 35 children (76.1%) belonged to Group A and 11 children (23.9%) belonged to Group B.Conclusion Our study shows that there is a higher prevalence of CSOM among undernourished children than in normal children. High prevalence of CSOM in undernourished children is a preventable health problem that needs health education and active intervention.
Keywords: chronic suppurative otitis media; undernourished children; prevalence